Liparis vivipara (Orchidaceae: Malaxideae), a new species from China: evidence from morphological and molecular analyses - Huang, Hui-Xia; Chen, Li-Jun; Liu, Zhong-Jian; Li, Ming-He (Phytotaxa, 2018)
A new orchid species, Liparis vivipara (Malaxidinae, Malaxideae, Epidendroideae), from Yunnan Province, China, is illustrated and described based on morphological and molecular analyses. The new plant is remarkably characterised by the upper older pseudobulbs often bearing black bulbils. Molecular analyses of nrITS and plastid matK DNA support this new species as sister to L. formosana and L. odorata.